Balneolotherapy Features of Natural Thermal Source from Pertek (Turkey-Tunceli) Due to Its Some Chemical, Radioctivity and Biological Parameters - Erecevit Sönmez , Pinar (Progress in Nutrition, 2022)
It can also be defined as a discipline that reviews the factors of balneology or hydrotherapy, which are alternative treatment methods for public health, from chemical, biological and medical aspects. In this study, it was aimed to investigate whether the underground waters in the Pertek district of Tunceli province are suitable for balneology. Chemical, radioactivity analysis, microbiological quality, antimicrobial activities were determined in relation to natural groundwater and its ability to be a natural healing source was investigated. When the chemical content is examined, it was determined to be bromide amount is 0.24 mg / L, Iodine (I); 1.9 mg / L, sulfur (S); 0.02 mg / L, boron (B): 2676 µg / L, silicium (Si); 1.9 mg / L. With respect to the results, thermal water has the feature to be used in balneolotherapy. According to the results of the radioactivity analysis, alpha (α) is 0.15 Bq / L; Beta (β) is